2012
DOI: 10.1111/j.1476-5381.2012.01997.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of senescence in cancer cells by the G‐quadruplex stabilizer, BMVC4, is independent of its telomerase inhibitory activity

Abstract: BACKGROUND AND PURPOSETelomerase is the enzyme responsible for extending G-strand telomeric DNA and represents a promising target for treatment of neoplasia. Inhibition of telomerase can be achieved by stabilization of G-quadruplex DNA structures. Here, we characterize the cellular effects of a novel G-quadruplex stabilizing compound, 3,6-bis(4-methyl-2-vinylpyrazinium iodine) carbazole (BMVC4). EXPERIMENTAL APPROACHThe cellular effects of BMVC4 were characterized in both telomerase-positive and alternative le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…3B). Under the BMVC or BMVC4 conditions, no apparent cytotoxic effect was observed for up to 6 days (19,20). These results indicate that G-quadruplex stabilizers could reduce the expression of WNT1.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 58%
See 3 more Smart Citations
“…3B). Under the BMVC or BMVC4 conditions, no apparent cytotoxic effect was observed for up to 6 days (19,20). These results indicate that G-quadruplex stabilizers could reduce the expression of WNT1.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 58%
“…On the other hand, c-myc is also a downstream target gene of the Wnt/␤-catenin pathway. Previously we demonstrated that BMVC4 repressed the c-myc expression (19,20). Because a G-quadruplex forming sequence was also identified at the promoter region of c-myc, it is likely that the repressing effect of c-myc by BMVC4 might be through its own G-quadruplex forming sequence directly and through repressing WNT1 expressing indirectly.…”
Section: Bmvc and Bmvc4 Repressed Wnt1 Expression Through Stabilizingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, ALT can be viewed as a state of perturbed DNA synthesis. Thus, an armamentarium of DNA synthesis inhibitors, including newly developed PCNA and BLM inhibitors [113,114] and G-quadruplex stabilizing agents [115,116], may exploit vulnerabilities present in ALT cells.…”
Section: Therapeutic Outlook For Altmentioning
confidence: 99%